Frozen shoulder: subjects’ needs and perspectives and clinicians’ beliefs and management strategies: do they align? A cross-sectional study - Brindisino, Fabrizio; Sciscione, Sara; Andriesse, Arianna; Cioeta, Matteo; Struyf, Filip; Feller, Daniel (BMC musculoskeletal disorders, 2024)
Objective Physiotherapists (PTs) play a crucial role in managing individuals with Frozen Shoulder (FS), frequently being the first healthcare professionals involved in the treatment of this condition. Aim This study aimed to compare the beliefs, expectations, and perspectives of individuals with FS with the knowledge, skills, and strategies of PTs, highlighting similarities and differences. Method This study adhered to the Checklist for Reporting Results of Internet E-Surveys (CHERRIES). From May 1st to August 1st, 2023, a two-part survey was conducted involving PTs and individuals diagnosed with FS. The survey focused on comparing key areas such as clinical assessment, patient education, treatment expectations, and the psychological aspects of the patient-clinician relationship. Results A total of 501 PTs and 110 subjects with FS participated in the survey. Most PTs showed proficiency in FS pathoanatomical conditions and were also attentive to psychological aspects (88.4%), describing the pathology evolution in three or two stages (68.2%). They also highlighted the importance of patient education (89.6%) and recognized the potential benefits of a multiprofessional collaboration in managing FS (82.2%). Reassurance was reported as a priority by 32.3% of PTs. Subjects with FS expressed a preference for PTs who are both expert and empathetic (73.6%). Regarding their understanding of FS, 29.09% of subjects reported receiving a three-phase explanation, while 26.36% felt inadequately informed. Nearly half of the subjects (49.09%) anticipated being managed independently by a PT, with 93.64% prioritizing the improvement of their range of motion. Conclusion This study revealed a general agreement between subjects with FS and PTs regarding aspects of the therapeutic relationship, patient education, pathology management, compliance and motivation strategies, and pain management preferences. However, significant differences emerged concerning the perception of physiotherapy effectiveness, primary treatment goals, subjects’ priorities, and the importance of psychological assessment. Impact statement Physiotherapists and subjects suffering from frozen shoulder showed considerable differences in their perception of physiotherapy effectiveness, primary treatment goals, subjects’ priorities, and the importance of psychological assessment. It is crucial for physiotherapists to delve deeper into the psychological dimension of subjects with FS in order to fully understand their needs and expectations. By incorporating individuals’ priorities and psychological assessments into a multiprofessional care approach, physiotherapists can improve treatment adherence and outcomes, ultimately increasing the overall patient satisfaction.